Power Struggle between China and the United States: Lessons of History - L. Estachy (Vestnik MGIMO-Universiteta)
Fernand Braudel, the economic historian, gave a key for reading the power struggles occurring today between the United States and China. «Just as a country at the center of a world-economy can hardly be expected to give up its privileges at international level, how can one hope that the dominant groups who combine capital and state power, and who are assured of international support, will agree to play the game and hand over to someone else?» In other words, the ruling circles in the United States, the hegemonic power of today, want to keep their leadership, China, the rising and challenging power, would like to replace the USA as the hegemonic country: the trade war starting in 2018 should be analysed in this context . The paper will deal with the recent developments of this hegemonic struggle: within the American establishment, the Pentagon and the US Department of Commerce have regained control over «Wall Street» which has resulted in an updated version of the US military-industrial complex, with China replacing the USSR in a new "cold war". Complex strategies are developped on both sides, involving manufacturing, technology, trade, financial, diplomatic and military issues. Referring to this geo-economic key for reading, a number of actions taken by the US government since 2018 aims in particular at checking China’s mounting economic and financial power. For the United States, it is about challenging the development of China’s influence in the world, in particular along the new maritime Silk Roads.